Implementasi Kebijakan Pemerintah Melalui Program Usaha Mikro Kecil dan Menengah pada Bank - Andi Irdan Atjo Mea; Zulkarnain Umar; Muhlis Hafel; Anfas Anfas (IPM2KPE, 2022)
This study aims to describe the implementation of the policies offered by Edward III, namely the communication model, resources, disposition, and bureaucratic structure through the Micro, Small and Medium Enterprises (UMKM) program at BRI's Majene Branch Office. The method used is qualitative with phenomenological research type. The data analysis used is descriptive qualitative. The results show that the implementation of government policies through the MSME program at the BRI Majene Branch Office includes, 1) the communication model in implementing government policies through the MSME program at the BRI Majene Branch, can be realized properly through effective communication between BRI officers and MSME actors according to the provisions laid down. has been mutually agreed; 2) the resource model in implementing government policies in the MSME sector can run smoothly because it is supported by professional and reliable human resources; 3) the disposition model in implementing government policies in the MSME sector, namely the character, attitude or behavior of the implementor where the main character expected is honesty. In this case, the attitude and character of the BRI Branch Majene officers in providing services are very professional and sympathetic, so that MSME actors are enthusiastic to develop their business honestly and transparently, because the key to success lies in honesty and trust, and 4) the model of the bureaucratic structure in implementing government policies. in the MSME sector, it was found that the MSME implementation mechanism at the BRI Majene Branch was made very simple and easily understood by customers, especially MSME players, where the organizational structure of the BRI Majene Branch Office was also quite adequate, namely Branch Managers, Assistant Marketing Managers, Unit Heads, and Materials. In conclusion, the implementation of government policies through the MSME program at the BRI Majene Branch Office includes, a) communication in implementing government policies through the Micro, Small and Medium Enterprises (UMKM) program at the BRI Majene Branch Office, based on the facts in the field that it has not run optimally because there are still many people who do not know about the existence of KUR credit which is relatively very helpful for additional capital with relatively very low interest rates for MSME entrepreneurs; b) resources in implementing government policies through the MSME program at BRI's Majene Branch Office, still limited resources and human resource development so that KUR credit marketing can run well so that remote areas far from BRI Kanca Majene can be served properly; c) disposition in implementing government policies through the MSME program at BRI's Majene Branch Office, which is related to the attitude of field officers who have not been optimally where there are still many complaints from customers regarding the credit process which is still considered slow by customers; d) bureaucratic structure in implementing government policies through the MSME program at BRI's Majene Branch Office, covering two things, namely the mechanism for implementing the MSME program in accordance with standard operating procedures (SOP) and the organizational structure of BRI's Majene Branch Office. at the BRI Majene Branch, it is made very simple and easy to understand by customers, especially MSME players, but regarding the administration of local government still needs to be addressed such as processing business certificates for completeness. Keywords: Implementation, Policy, Micro, Small and Medium Enterprises